Analisis Hasil Belajar Matematika Siswa Sekolah Dasar Kota Palu Pada Masa Pandemi Covid-19 - Kertayasa, I Ketut (Perspektif Ilmu Pendidikan, 2022)
Abstract: The research aims to know the achievement of learning outcomes and the factors that influence it. The research method used was descriptive qualitative research. The research subjects were 223 students of grade VI SD at Palu city. Data collection techniques were carried out are tests and interviews. The results obtained from the research that has been done are that of the 223 students who took the test, only 52 students (23%) correctly answered the short answer questions and only 7 students (3%) were able to answer the essay questions about the circumference of plane materials. The learning outcomes of Palu City Elementary School students are in the poor category. From the results of interviews with students, teachers, and school principals, information was obtained that the factors causing low learning outcomes during the COVID-19 pandemic were the decreased level of student discipline, the difficulty of controlling students and teachers, BDR for a long time caused students to easily forget, absorb low online face-to-face material, excessive public concern about COVID-19, support from parents and the unequal economy of parents. Keywords: analysis, mathematics learning outcomes, COVID-19 pandemic